2020
DOI: 10.1126/science.aaz4352
|View full text |Cite
|
Sign up to set email alerts
|

TTC5 mediates autoregulation of tubulin via mRNA degradation

Abstract: Tubulins play crucial roles in cell division, intracellular traffic, and cell shape. Tubulin concentration is autoregulated by feedback control of messenger RNA (mRNA) degradation via an unknown mechanism. We identified tetratricopeptide protein 5 (TTC5) as a tubulin-specific ribosome-associating factor that triggers cotranslational degradation of tubulin mRNAs in response to excess soluble tubulin. Structural analysis revealed that TTC5 binds near the ribosome exit tunnel and engages the amino terminus of nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 52 publications
8
99
0
Order By: Relevance
“…Opposing changes in STK11 protein and mRNA levels could reflect homeostatic control of this powerful signaling pathway. Translation-dependent feedback of some other proteins is known to reduce mRNA levels through nonsense-mediated decay ( Giorgi et al, 2007 ; Paolantoni et al, 2018 ) or other forms of mRNA degradation ( Lin et al, 2020 ; Shoshani and Cleveland, 2020 ). Complex feedback control involving changes in RNA export and stability has also been described for MAP kinase signaling ( Sugiura et al, 2003 ; Prieto-Ruiz et al, 2020 ), but whether this type of regulation exists for Stk11 and the AMP-related kinase pathway remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Opposing changes in STK11 protein and mRNA levels could reflect homeostatic control of this powerful signaling pathway. Translation-dependent feedback of some other proteins is known to reduce mRNA levels through nonsense-mediated decay ( Giorgi et al, 2007 ; Paolantoni et al, 2018 ) or other forms of mRNA degradation ( Lin et al, 2020 ; Shoshani and Cleveland, 2020 ). Complex feedback control involving changes in RNA export and stability has also been described for MAP kinase signaling ( Sugiura et al, 2003 ; Prieto-Ruiz et al, 2020 ), but whether this type of regulation exists for Stk11 and the AMP-related kinase pathway remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the mutated tubulin produced could be unstable and/or unable to assemble into MTs, so that in effect, mutations therefore behave as typical 'loss‐of‐function' mutations. In this case, one could imagine that transcomplementation would occur with the intact allele, as well as with other isoforms, as suggested by the data showing that cells can detect and strikingly maintain soluble tubulin concentration [49–51]. Indeed, this is what is observed when both alleles of the neuronal gene TUBB3 are deleted in mice with no detectable variation in ÎČ‐tubulin level [167].…”
Section: Resultsmentioning
confidence: 99%
“…showed early on that a sudden increase in the free tubulin pool of cells treated with specific MT inhibitors leads to a rapid decrease in tubulin synthesis [49]. More recently, it was shown that quiescent cells are able to detect both subtle and strong perturbations in MT dynamics, and to maintain the concentration of soluble tubulin through cotranslational degradation of excess tubulin RNA by a ribosomal protein, TTC5 [50,51].…”
Section: Microtubule Basics Dynamic Instability and Partnersmentioning
confidence: 99%
“…Tubulin mRNAs are co-translationally degraded in cells with excess soluble subunits (Cleveland et al, 1981;Lin et al, 2020). TUBA4A and TUBB4A are 4EHP and GIGYF1/2 target mRNAs (Tables S2, S3, and S4).…”
Section: Tubulin Mrnas Are Regulated By Gigyf1/2mentioning
confidence: 99%